Juridical Analysis For Notaries Who Hold Concurrent Positions As Curators And Other Positions According To Law Number 2 Of 2014 Conerning Notary Positions - Mustafidah, Aqidatul (International Significance of Notary, 2023)
Abstract : a notary is a public official who has the authority to make authentic deeds and has other authorities based on article 1 paragraph 1 of law number 2 of 2014 concerning the position of notary, and a curator is an inheritance office or individual appointed by the court to manage and settle the debtor's assets bankrupt under the supervision of a supervisory judge based on law number 37 of 2004 concerning bankruptcy and PKPU. If bankruptcy occurs in a company, the notary is in charge of making deeds including the company deed and acts as a curator in that position. This research is normative juridical research. By using a statutory approach, the sources of legal materials obtained are secondary, primary and tertiary legal materials consisting of statutory books, journals, papers. notaries are prohibited from carrying out positions outside their area of office; Leaving his/her area of office for more than 7 (seven) consecutive working days without a valid reason; Concurrently as a civil servant; Concurrently serving as a State official; Holding a position as leader or employee of a State-owned enterprise, regional-owned enterprise or private enterprise; Concurrently serving as Land Deed Drafting Official and/or Class II Auction Official outside the Notary's place of residence; Become a Substitute Notary; Carrying out other work that is contrary to religious norms, morality or propriety which could affect the honor and dignity of the notary's position. The legal consequences are receiving sanctions in the form of a written warning, temporary dismissal, honorable dismissal, or dishonorable dismissal.Keywords : Notary, Curator, Concurrent Positions